A search for an excited muon decaying to a muon and two jets in pp collisions at √ s = 8 TeV with the ATLAS detector - Onofre, A. (2016)
A new search signature for excited leptons is explored. Excited muons are sought in the channel ${pp}→ μ {μ }^{* }→ μ μ \ {\rm{jet}}\;{\rm{jet}}$, assuming both the production and decay occur via a contact interaction. The analysis is based on 20.3 fb−1 of pp collision data at a centre-of-mass energy of $\sqrt{s}\;=\;8\;{\rm{TeV}}$ taken with the ATLAS detector at the large hadron collider. No evidence of excited muons is found, and limits are set at the 95% confidence level on the cross section times branching ratio as a function of the excited-muon mass ${m}_{{μ }^{* }}$. For ${m}_{{μ }^{* }}$ between 1.3 and 3.0 TeV, the upper limit on $σ B({μ }^{* }→ μ q\bar{q}$) is between 0.6 and 1 fb. Limits on $σ B$ are converted to lower bounds on the compositeness scale Λ. In the limiting case ${\rm{Λ }}={m}_{{μ }^{* }}$, excited muons with a mass below 2.8 TeV are excluded. With the same model assumptions, these limits at larger ${μ }^{* }$ masses improve upon previous limits from traditional searches based on the gauge-mediated decay ${μ }^{* }→ μ γ $.